From Large Zones to Small Terranes to Detailed Reconstruction of an Early to Middle Ordovician Arc – Backarc System Preserved Along the Iapetus Suture Zone: A Legacy of Hank Williams - Zagorevski, A.; McNicoll, V.; van Staal, C.R.; Kerr, A.; Joyce, N. (Geoscience Canada, 2015)
The Annieopsquotch accretionary tract (AAT) comprises a thrust stack of Lower to Middle Ordovician arc and backarc terranes that were accreted to the composite Laurentian margin of Iapetus during the Middle to Late Ordovician. Geological relationships suggest that the constituent terranes of the AAT initially formed outboard of the composite Laurentian margin in an extensional arc that underwent multiple rifting episodes prior to its accretion. The initiation of AAT magmatism led to the development of Tremadocian to Floian supra-subduction zone ophiolites (481 to 477 Ma) with organized ridges indicated by the presence of well-developed sheeted dyke complexes. This spreading centre propagated through a fragment of Laurentian crust and separated it from the composite Laurentian margin. This Laurentian crust fragment then formed the basement to subsequent Floian to Darriwilian AAT arc magmatism. The Floian arc (473 to 468 Ma) underwent extensive rifting indicated by organized spreading in the Lloyds River backarc basin, which was floored by juvenile backarc ophiolitic crust (472 Ma). The establishment of the Darriwilian arc (467 to 462 Ma) was in part coeval with yet another stage of rifting. Darriwilian magmatism is characterised by significant along-strike variability, ranging from continental to primitive calcalkaline arc to tholeiitic backarc-like magmatism. The diversity of Darriwilian magmatism can be attributed to fragmentation and magmatic reworking of Laurentian-derived basement along strike in the same arc undergoing disorganized spreading. The development of the AAT is interpreted to be similar to that of the modern Izu – Bonin – Mariana arc in the western Pacific.